California Maritime Academy Observes 25th Anniversary - Vallejo Times-Herald (Vallejo Times-Herald)
The California Maritime Academy, located in Morrow Cove near Vallejo, this year is observing the 25th anniversary of its founding. The academy, known originally as the Calfornia State Nautical School, was authorized by the 1929 session of the Legislature and became a part of the state college system when Governor C. C. Young signed the legislation for its establishment.